Fluorescent probes based on the core–shell structure of molecular imprinted materials and gold nanoparticles for highly selective glutathione detection. Issue 48 (5th December 2022) - Wu, Guoli; Zhao, Yongdan; Li, Xiaofang; Lu, Xiaolin; Qu, Tingli
Abstract : Glutathione fluorescent probes based on core–shell structures containing fluorescent dyes, molecularly imprinted materials, and gold nanoparticles are suitable for glutathione sensing in complex materials (such as serum). Abstract : Glutathione (GSH) is a polypeptide with important physiological functions. Real-time and accurate detection of GSH is of great significance for clinical diagnosis, disease treatment and pathogen detection. A fluorescent nanosensor based on composite core–shell nanoparticles for the highly selective detection of GSH is reported. In the cores, the fluorescence of rhodamine b was quenched by using gold nanoparticles (AuNPs), and GSH could competitively combine with AuNPs to cause rhodamine b to fall off, thereby recovering the fluorescence. In the shell part, molecularly imprinted materials using oxidized glutathione (GSSG) as a pseudotemplate provide GSH/GSSG specific pores and improve the specificity and anti-interference ability of the sensor. The GSH sensor has a detection range of 0–100 μM and limit of detection (LOD) of 0.18 μM, and robust sensing performance in fetal bovine serum, indicating its great potential for clinical diagnosis.